UPAYA KEPALA SEKOLAH SEBAGAI SEORANG MANAGER DALAM MENINGKATKAN PROFESIONALITAS GURU - Hernik Khoirun Nisak (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2022)
Management is often defined as science, tips and professions. It is said to be a science by Luther Gulick because management is seen as a field of knowledge that systematically seeks to understand why and how to work together. It is said to be a tip by Follet because management achieves goals through means by arranging other people to carry out tasks. Seen as a profession because management is based on special skills to achieve a manager's achievement, and professionals are guided by a code of ethics. The principal as an education administrator is responsible for the smooth implementation of education and teaching in his school. Therefore, to be able to carry out their duties properly, school principals should understand, master, and be able to carry out activities related to their functions as educational administrators. The teaching profession is not just a vehicle to channel hobbies or as a job that must be occupied to realize professional expertise to the fullest. As professionals, teachers play important roles and responsibilities in the implementation of teaching programs in schools. Teachers are also fully responsible for the achievement of teaching goals in schools. The teacher is a student mentor so that both of them can establish a meaningful emotional connection during the process of absorbing values ??from the surrounding environment. This condition makes it easier for them to adjust to life in society. Efforts to improve the quality of teachers and teacher education have long been the commitment of the Ministry of Education and Culture. One of the targets of these efforts is to improve the ability of teachers to plan and implement lessons. The achievement of these targets must be seen from the increasing professionalism of teachers and optimally increasing in the learning process with students.